2022
DOI: 10.1155/2022/3180871
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Kangaroo Mother Care Intervention on Immunological and Pulmonary Functions of Preterm Infants during Breastfeeding

Abstract: Objective. Preterm infants (PTIs) are prone to respiratory failure or other diseases due to immature organ development and poor immunological function. Herein, the effects of Kangaroo Mother Care (KMC) on the immunological and pulmonary functions of PTIs during breastfeeding were investigated in this study. Methods. The study recruited 86 delivery women and their PTIs with preterm pregnancy outcomes, consisting of 46 cases receiving breastfeeding plus KMC intervention (KMC group) and 40 cases receiving breastf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…More so, nursing students in this study assisted mothers to practice KMC (82.4%) and practice of kangaroo mother care effectively implemented in facilities 74.6% and continuously. These results in the current study are in line with what was earlier mentioned in a study by (Yang et al, 2022) where nurses and other healthcare workers ensured that mothers carried out KMC correctly by observing them during the procedure. In addition, the behavior of nurses during clinical training is used to witness return demonstrations to be sure if knowledge has been communicated or not.…”
Section: The Practice Of Nursing Students Towards Kmcsupporting
confidence: 92%
“…More so, nursing students in this study assisted mothers to practice KMC (82.4%) and practice of kangaroo mother care effectively implemented in facilities 74.6% and continuously. These results in the current study are in line with what was earlier mentioned in a study by (Yang et al, 2022) where nurses and other healthcare workers ensured that mothers carried out KMC correctly by observing them during the procedure. In addition, the behavior of nurses during clinical training is used to witness return demonstrations to be sure if knowledge has been communicated or not.…”
Section: The Practice Of Nursing Students Towards Kmcsupporting
confidence: 92%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%